2015
DOI: 10.1162/jocn_a_00691
|View full text |Cite
|
Sign up to set email alerts
|

Prior Experience Biases Subcortical Sensitivity to Sound Patterns

Abstract: To make sense of our ever-changing world, our brains search out patterns. This drive can be so strong that the brain imposes patterns when there are none. The opposite can also occur: The brain can overlook patterns because they do not conform to expectations. In this study, we examined this neural sensitivity to patterns within the auditory brainstem, an evolutionarily ancient part of the brain that can be fine-tuned by experience and is integral to an array of cognitive functions. We have recently shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 90 publications
(109 reference statements)
1
24
0
Order By: Relevance
“…The word segmentation paradigm is frequently used to examine the neural basis underlying SL (e.g., [ 34 , 41 , 43 , 44 , 46 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]). This paradigm basically consists of a concatenation of pseudo-words ( Figure 2 a).…”
Section: Mathematical Interpretation Of Brain Sl Process Shared Bymentioning
confidence: 99%
See 1 more Smart Citation
“…The word segmentation paradigm is frequently used to examine the neural basis underlying SL (e.g., [ 34 , 41 , 43 , 44 , 46 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]). This paradigm basically consists of a concatenation of pseudo-words ( Figure 2 a).…”
Section: Mathematical Interpretation Of Brain Sl Process Shared Bymentioning
confidence: 99%
“…Finally, the effects of SL manifest as a difference in the ERP and ERF amplitudes between stimuli with lower and higher TPs ( Figure 4 ). Although many studies of word segmentation detected SL effects on the N400 component [ 43 , 46 , 88 , 89 , 93 , 94 , 105 ], which is generally considered to reflect a semantic meaning in language and music [ 106 , 107 , 108 ], auditory brainstem response (ABR) [ 96 ], P50 [ 41 ], N100 [ 94 ], mismatch negativity (MMN) [ 40 , 44 , 98 ], P200 [ 46 , 89 , 105 ], N200–250 [ 44 , 47 ], and P300 [ 83 ] have also been reported to reflect SL effects ( Table 1 ). In addition, other studies using Markov models also reported that SL is reflected in the P50 [ 14 , 36 , 37 ], N100 [ 10 , 14 , 32 , 35 ], and P200 components [ 35 ].…”
Section: Neural Basis Of Statistical Learningmentioning
confidence: 99%
“…Infants quickly learn statistical regularities in the acoustic environment, and this is thought to contribute to language acquisition [52]. But not even these ostensibly passive learning processes are exempt from cognitive influence: prior experience and active expectations guide statistical learning [53,54]. Thus, as young as infancy, listeners can connect incoming sounds to meaning, and also exert meaning on incoming sounds, reinforcing the interplay between sensorimotor and cognitive systems in auditory learning.…”
Section: Sensorimotor Influences On Auditory Processingmentioning
confidence: 99%
“…There is compelling empirical evidence supporting the view that language (or music) experience enhances neural representation of temporal attributes of pitch that are behaviorally relevant at both cortical and subcortical levels (Gandour & Krishnan, 2014; Gandour & Krishnan, 2016; Intartaglia et al, 2016; Krishnan et al, 2012a; Skoe et al, 2015; Song et al, 2008; Wong et al, 2007; Zatorre & Gandour, 2008; Zatorre & Baum, 2012). …”
Section: Introductionmentioning
confidence: 99%